The Role of Mitotic Kinases and the RZZ Complex in Kinetochore-Microtubule Attachments: Doing the Right Link - Barbosa, João; Sunkel, Claudio E.; Conde, Carlos (Frontiers in Cell and Developmental Biology, 2022)
During mitosis, the interaction of kinetochores (KTs) with microtubules (MTs) drives chromosome congression to the spindle equator and supports the segregation of sister chromatids. Faithful genome partition critically relies on the ability of chromosomes to establish and maintain proper amphitelic end-on attachments, a configuration in which sister KTs are connected to robust MT fibers emanating from opposite spindle poles. Because the capture of spindle MTs by KTs is error prone, cells employ mechanisms that sense and correct inaccurate KT-MT interactions before committing to segregate sister chromatids in anaphase. If left unresolved, these errors can result in the unequal distribution of chromosomes and lead to aneuploidy, a hallmark of cancer. In this review, we provide an overview of the molecular strategies that monitor the formation and fine-tuning of KT-MT attachments. We describe the complex network of proteins that operates at the KT-MT interface and discuss how AURORA B and PLK1 coordinate several concurrent events so that the stability of KT-MT attachments is precisely modulated throughout mitotic progression. We also outline updated knowledge on how the RZZ complex is regulated to ensure the formation of end-on attachments and the fidelity of mitosis.